The properties of adolescent inhalant abuse in sought-east of anatolia - Yaşan, Aziz; Gürgen, Faruk (Journal of Dependence, 2004)
Objective: Inhalant abuse is a common problem among adolescents in the world and in our country. We also observe inhalant abuse in our region frequently. However, in the literature, we did not come across to any study regarding properties of adolescent inhalant abuse in South-East Anatolian region. We planned this study to determine the properties of adolescent inhalant abuse in our region. Method: We met 113 inhalant abuser adolescents in their places inhalant use in the evenings. 37 cases who accepted to participate were invited to another location where appropriate conditions were provided. Their sociodemographic and inhalant abuse properties were determined by a previously prepared form during one to one interviews. Results: The median age for inhalant abuse cases was 13.8. It was 10.8 for starting inhaler agents. All of the cases were using the inhalant glue, Bally. 83.5% of the cases had left school, 35.1% had legal problem for various reasons. They were either working or stealing to find money for inhalant agents. 54% of cases had no health insurance. Conclusion: There are inhalant abuse problems in our region. The majority of adolescent who abuse inhalants has no access to treatment. Therefore, the establishment of UMATEM is necessary for prompt treatment of inhalant abuse in our region.